Histomorfologija in imunohistologija postinfekcijskega glomerulonefritisa v odvisnosti od trajanja bolezni in vrste okužbe - Hermann, Dejan (Medicinski razgledi, 1999)
In addition to the classical picture of endocapillary proliferative and exudative glomerulonephritis, patients with acute postinfectious glomerulonephritis may manifest a broad spectrum of various histomorphologicaland immunohistological changes which may reflect the stage of the disease, their responsivness to the disease and/or the specific type ofinfection. The data on the correlation between histomorphological changes and immune deposits are still sparse. The purpose of this study was to evaluate these, most probably key relationships in the pathogenesis related tothe duration of the disease and type of infection. This retrospective study involved 113 kidney biopsies from 91 men and 22 women with the diagnosis of postinfectious glomerulonephritis. The tissue samples were examined by standard light and immunofluorescent microscopy techniques. Mesangial, endocapillary and mesangiocapillary proliferation, exudation, tubulo-interstitial changes, vascular lesions and glomerular immune deposits were evaluated semiquantitatively using the generally recognized nephropatological methods. Extracapillary proliferation and global and segmentglomerulosclerosis were evaluated as a percentage of the affected glomeruli. Immune deposits demonstrated the following three immunofluorescent patterns: garland, starry sky and mesangial.
Keywords: Glomerulonephritis; ledvice; Pathology; glomerulonefritis; Immunology; imunologija; infekcije; Streptococcal infections; Complications; Fluorescent antibody technique, direct; Antigen-antibody complex; diagnostika